Specifying the Multidimensionality of Solar Energy Acceptance and Its Determinants: Focusing on the Moderating Effect of Innovation Diffusion Factors - 구자필; 김서용; 김수빈 (Journal of Safety and Crisis Management, 2024)
As the issue of climate change becomes more serious, renewable energy is gaining increasing attention. Solar energy, in particular, is one of the most technologically advanced renewable energy sources. However, the problem of solar energy acceptance is acting as a stumbling block to the spread of solar energy. This study focuses on the multidimensionality of solar energy acceptance, categorizing it into the intention to install solar energy at home (individual level) and the intention to participate in solar energy cooperatives (citizen participation). Variables based on energy citizenship and innovation diffusion theory are utilized as independent variables. According to survey-based analysis, significant factors influencing the intention to install solar energy at home are: relative advantage > problem awareness > observability > complexity > accountability > rights awareness. For cooperative participation, the order is: relative advantage > observability > accountability > problem awareness. Relative advantage plays a decisive role in both cases. Additionally, relative advantage and observability enhance the positive effect of rights consciousness on the intention to install home solar facilities.
Keywords: solar energy acceptance; energy citizenship; diffusion of innovations theory; multidimensionality of acceptance